The Role of Green Marketing in Energy Conservation in the Domestic Sector - Shukla, Pranjjal; Paul, Dipen; Malik, Sushant; Mishra, Dharmesh K. (International Journal of Energy Economics and Policy, 2020)
India now ranks 3rd after China and USA in the Primary Energy consumption. One of the sectors which have shown a sharp increase in the domestic sector. Keeping in mind the impacts on the environment and associated expenses, reduction in energy consumption in this sector is an important domain of research. The paper aims to analyse the role of Green Marketing and its tools in affecting the Energy-saving and Green Product Buying behaviour in the Domestic Sector. The factors considered for the analysis seem to have strong correlation hence Descriptive Statistics doesn’t give a clear picture. Therefore a more advanced market research tool such as factor analysis helps in understanding the factor loadings. At the same time, an effort made is to understand whether price or Environmental Concern plays a pivotal role in buying an Energy-efficient appliance. The research proves the significance of Green marketing in influencing the buying Behaviour and Energy-saving behaviour as Respondents claim they are highly influenced by Green Packaging and Environmental Beliefs. It can also be noted that although advertising plays a good role in spreading awareness amongst respondents, it is not a significant factor to change their perception regarding the purchase of Green products. Recommendations are made to augment the extent of exploration in the study of Green marketing and its role in energy-saving behaviour. Keywords: Consumer Behaviour, Environmental Belief, Energy Saving, Green Marketing JEL Classifications: G2, M3, O4 DOI: https://doi.org/10.32479/ijeep.10567